TEKNOLOGI LITIK DI SITUS TALIMBUE, SULAWESI TENGGARA: TEKNOLOGI BERLANJUT DARI MASA PLEISTOSEN AKHIR HINGGA HOLOSEN - Suryatman; Sue O’ Connor; David Bulbeck; Ben Marwick; Adhi Agus Oktaviana; Unggul Prasetyo Wibowo (Badan Riset dan Inovasi Nasional, 2016)
Abstract. The Lithic Technology at Talimbue Site, Southeast Sulawesi: Continuing Technology from Late Pleistocene up to Holocene Periods. The Talimbue site at Southeast Sulawesi is packed with lithic and these offer a new perspective on the lithic technology of Sulawesi. The absence of information on the prehistoric lithic technology of Southeast Sulawesi is a factor of interest that makes research on knowledge of the Talimbue site necessary. Lithic artefacts were manufactured from the terminal Pleistocene to the Late Holocene. This research will disentangle the details of the lithic technology at the Talimbue Site. The analyzed flaked stone artefacts fall into 3 categories, which are retouched flakes, debitage and cores. For its part, debitage was classified into 3 categories, which are complete flakes, broken flakes and debris. The retouch index was also measured so as to provide a quantitative estimate of the level of retouch intensity of the retouched flakes. The results of the analysis indicate changes in the stone flake technology during the period of occupation of the Talimbue Site. The change of technology occurs because the process of adaptation caused by a change of environment. Keywords: Lithic, Technological change, Period of occupation Abstrak. Temuan litik yang sangat padat di Situs Talimbue di Sulawesi Tenggara menunjukkan sebuah persepektif baru dalam kajian teknologi litik di Sulawesi. Kekosongan informasi teknologi litik masa prasejarah di wilayah Sulawesi Tenggara adalah hal yang menarik dikaji dalam penelitian di Situs Talimbue. Artefak litik digunakan dari masa Pleistosen Akhir hingga masa Holosen Akhir. Penelitian ini akan menguraikan secara detail bagaimana teknologi litik di Situs Talimbue. Artefak batu diserpih yang dianalisis menjadi 3 kategori, yaitu serpih diretus, serpihan dan batu inti. Serpihan kemudian diklasifikasi menjadi 3 kategori, yaitu serpih utuh, serpih rusak dan tatal. Pengukuran indeks retus juga dilakukan bertujuan untuk mengestimasi secara kuantitatif tingkat intensitas retus terhadap serpih yang telah diretus. Hasil penelitian menunjukkan perubahan teknologi artefak batu diserpih terjadi selama masa hunian di Situs Talimbue. Perubahan teknologi terjadi karena adanya proses adaptasi yang disebabkan oleh perubahan lingkungan. Kata Kunci: Litik, Perubahan teknologi, Fase hunian